EBOOK VERSUS WEBINAR: STUDI EMPIRIS TENTANG PERSEPSI DOSEN TERHADAP DUKUNGAN PEDAGOGIS DALAM INTEGRASI VOICETHREAD - Rina Ari Rohmah (CV.Karoteh Utama, 2025)
The use of digital learning technologies in higher education remains limited, including the adoption of VoiceThread as a collaborative platform. This study aimed to evaluate the effectiveness of an eBook compared to a webinar as pedagogical support for faculty. Using an action research approach with a quasi-experimental design, two groups of faculty participated: one using an eBook and the other attending a webinar. Data were collected through a survey based on the Decomposed Theory of Planned Behavior (DTPB) and analyzed using independent-samples t-tests along with content analysis. Results indicated no significant difference between the groups in pedagogical perceptions of VoiceThread. However, the eBook was valued for its flexibility, accessibility, and support for self-directed learning, while the webinar was appreciated for providing real-time interaction. The findings suggest that content quality outweighs delivery format, and eBooks can serve as an innovative alternative, though complemented by collaborative strategies for sustainable adoption.